THE DECLARATION OF ENVIRONMENTAL ACCEPTABILITY OF ROAD FREIGHT TRANSPORT (Perner's Contacts, 2013)
Into contractual relations in road transport within the responsibility of the carrier there are added the requirements for environmental acceptability of vehicles in terms of perform emission limits but also requirements for declaring of impacts of traffic operations on the environment in terms of proving the quantity of selected pollutants emitted in the exhaust which are produced. It can be, for example, the record about the amount of excreted carbon dioxide into the atmosphere (the record about CO2).
Keywords: road freight transport; environment; declaration; emissions